The Relationship Between Body Mass Index (BMI) And Physical Fitness Of Students At SD N 1 Labuhan Ratu Bandar Lampung Post-Pandemic Covid-19 - Surisman; Heru Sulistianta; Muhammad Rivaldo; Marta Dinata (Jurnal Pendidikan Jasmani (JPJ), 2023)
This study aims to determine the magnitude of the relationship between body mass index (BMI) and the physical fitness of students of SD N 1 Labuhan Ratu, Bandar Lampung City. This research uses a survey method with a correlational quantitative approach. The population used is class V with a total of 40 students. The sampling technique used total sampling consisting of 23 sons and 17 daughters. Body mass index (BMI) instruments, namely digital scales and height measuring devices, then physical fitness used the TKJI test for ages 10-12 years. Data analysis used the product moment correlation test. The results of this study indicate that there is a relationship between body mass index (BMI) and the physical fitness of SD N 1 Labuhan Ratu students in Bandar Lampung city which can be seen from the interpretation criteria for the correlation coefficient r, namely the value rx.y = 0.768 is strong for boys and rx.y = 0.562 is for women. Moderate results for women because their level of physical fitness is low and for men their level of physical fitness is strong. These results are because gender is a factor that affects physical fitness. So the conclusion is that there is a relationship between body mass index (BMI) and physical fitness for both boys and girls, but for male students the relationship is stronger while for female students the relationship is moderate.